Maqosid Al-Syari’ah Sebagai Dasar Pergerakan Ekonomi Syariah Di Era Digital - Maulana, Lutfi; Mumtahaen, Ikmal; Nugraha, AA Willy; Hasanah, Uswatun; Fitriana, Nadia (International Conference on Islamic Economic (ICIE), 2023)
In today's all-digital era, the behavior or culture of the Indonesian people has changed to meet their needs. Changes in behavior or culture sometimes occur not only in the form of continuous innovation but also sometimes in the form of disruptive and destructive innovations. This type of research is normative research using a library research approach. The results of the study show that the implementation of an all-digital modern economic system is a primary need (dharuriyat), at least to meet secondary needs (hajiyat), so that the Indonesian Muslim community must do so not only in a sustainable form. innovation, but also disruptive innovation implemented in the digital economic system to guarantee the security of public rights (hifdz almujtama') and build economic progress as the application of one of the maqosidh sharia principles, namely safeguarding wealth (hifdz al-mal).